Interventional treatment combined with immunotargeted therapy in unresectable combined hepatocellular-cholangiocarcinoma: a real-world retrospective cohort study - Lin, Yan-Song; Wu, Li-Yan; Lin, Li-Hui; Yang, Xia; Liu, Fang-Yi; Wu, Yan-Qin; Ding, Zhen; Liang, Yu-Jing; Yun, Jing-Ping (Frontiers in Immunology, 2025)
BackgroundEvidence-based treatment for unresectable combined hepatocellular-cholangiocarcinoma (cHCC-CCA) has not been established. This study aimed to assess the effectiveness and safety of interventional treatment combined with immunotargeted therapy (IIT) in unresectable cHCC-CCA patients.MethodsPatients with a histological diagnosis of unresectable cHCC-CCA who received IIT therapy from January 2019 to March 2024 were retrospectively enrolled. The study evaluated overall survival (OS), progression-free survival (PFS), tumor responses and safety.ResultsA total of 242 cHCC-CCA patients were screened and 51 patients were enrolled for analysis. The median follow-up duration was 15.8 months (95% CI: 12.0-19.7 months). The median OS was 17.8 months (95% CI: 12.4-23.2 months) and the median PFS was 8.9 months (95% CI: 5.8-12.0 months). For overall response, the objective response rate was 41.2% and 56.9% based on RECIST 1.1 and mRECIST, respectively. Patients with primary cHCC-CCA showed significantly prolonged OS (median OS: 21.4 months vs. 11.4 months, p = 0.011) and PFS (median PFS: 9.5 months vs. 4.1 months, p = 0.036) compared to those with recurrent cHCC-CCA. Patients with dominant HCC did not show significant differences for OS (p = 0.835) and PFS (p = 0.553) compared to those with dominant iCCA. Six patients (11.8%) experienced grade ≥3 adverse events, including leukopenia (n=1, 2.0%), neutropenia (n=1, 2.0%), thrombocytopenia (n=2, 3.9%), elevated alanine transaminase (ALT) (n=2, 3.9%), elevated aspartate aminotransferase (AST) (n=2, 3.9%), hypoalbuminemia (n=2, 3.9%), and hyperbilirubinemia (n=1, 2.0%). Immunotherapy was discontinued for two patients due to grade ≥3 elevations in ALT and AST.ConclusionThe triple combination of interventional treatment, PD-(L)1 inhibitor, and targeted therapy is an effective and safe approach for unresectable cHCC-CCA patients.